Study of optical bandgap and other related optical properties in amorphous thin films of some optical materials of Se-Te-Sn-Ag system. (June 2022) - Atyia, H.E.; Fouad, S.S.; Kumar Pal, Shiv; Srivastava, Ankita; Mehta, Neeraj
Highlights: Synthesis of novel-third generation glasses of SeTeSnAg system. Observation of correlation between structural stiffness in the amorphous network of thin-film samples. Tuning of optical properties by changing Ag composition. Suitable materials for utilization in optical devices and infrared sensing applications. Abstract: Recently, the STSA samples of Se78-x Te20 Sn2 Agx (x = 0, 2, 4, 6) system were synthesized by the classical melt-quench route to get them in bulk form in our laboratory for electrical/thermal characterization. Now, we have prepared their thin films (TFs) using physical vapor deposition for their optical characterization. The optical properties of as-prepared TFs have been examined through their experimental transmission spectra by choosing 400 nm to 2500 nm spectral range. Initially, we have determined the indices of refraction and the absorption of TFs. Next, we have calculated the optical band gap E g opt by applying Tauc's theory. The outcomes indicate that the value of E g opt is influenced intensely by the film composition. The linear dependency of photon energy that exists upon the absorption coefficient for the film gives Urbach energy Ee . The other parameters like loss functions of volume/surface energy, optical/electrical conductivity, and complex dielectric constant, were also determined. The increment in the value of the optical band gap with Ag incorporation in the parent SeTeSn (STS) system can be clarified by the binding energy of Se-Se and Se-Ag bonds.